Perioperative Neurofilament Light Plasma Concentrations and Cognition before and after Cardiac Surgery: A Prospective Nested Cohort Study. (19th August 2022) - Brown, Charles H.; Lewis, Alexandria; Probert, Julia; Parish, Michelle; Tian, Jing; Mandal, Kaushik; Everett, Allen; Colantuoni, Elizabeth; Kamath, Vidyulata; Hogue, Charles; Moghekar, Abhay
Abstract : Background: Neurofilament light is a marker of neuronal injury and can be measured in blood. Postoperative increases in neurofilament light have been associated with delirium after noncardiac surgery. However, few studies have examined the association of neurofilament light changes with postdischarge cognition in cardiac surgery patients, who are at highest risk for neuronal injury and cognitive decline. The authors hypothesized that increased neurofilament light (both baseline and change) would be associated with worse neuropsychological status up to 1 yr after cardiac surgery. Methods: This observational study was nested in a trial of cardiac surgery patients, in which blood pressure during bypass was targeted using cerebral autoregulation monitoring. Plasma concentrations of neurofilament light were measured at baseline and postoperative day 1. Neuropsychological testing was performed at baseline, 1 month after surgery, and 1 yr after surgery. Primary outcomes were baseline and change from baseline in a composite z-score of all cognitive tests. Results: Among 167 patients, cognitive outcomes were available in 80% (134 of 167) and 61% (102 of 167) at 1 month and 1 yr after surgery, respectively. The median baseline concentration of neurofilament light was 18.2 pg/ml (interquartile range, 13.4 to 28.1), and on postoperative day 1 was 28.5 pg/ml (interquartile range, 19.3 to 45.0). Higher baseline log neurofilament light was associated with worse baseline cognitive z-score (adjusted slope, –0.60; 95% CI, –0.90 to –0.30; P < 0.001), no change in z-score from baseline to 1 month (0.11; 95% CI, –0.19 to 0.41; P = 0.475), and improvement in z-score from baseline to 1 yr (0.56; 95% CI, 0.31 to 0.81; P < 0.001). Whereas some patients had an improvement in cognition at 1 yr and others a decline, an increase in neurofilament light from baseline to postoperative day 1 was associated with a greater decline in cognition at 1 yr. Conclusions: Higher baseline neurofilament light concentration was associated with worse baseline cognition but improvement in cognition at 1 yr. A postoperative increase in neurofilament light was associated with a greater cognitive decline at 1 yr. Abstract : In an observational study of 167 cardiac surgery patients nested within a randomized controlled study of blood pressure management, higher baseline neurofilament light concentration in blood is associated with worse baseline cognition, but improvement in cognition at 1 yr. An increase in neurofilament light on postoperative day 1 is associated with a greater decline in cognition at 1 yr.